Social innovation and temporary innovations systems (TIS): insights from nature-based solutions in Europe - Donnelly Cox, Gemma; Rhodes, Mary-Lee; McQuaid, Siobhán (My University, 2021)
Purpose – The purpose of this paper is to examine the applicability of the complexity-based temporary innovation system (TIS) framework to social innovation and examine the extent to which “nature-based solution” (NBS) projects may be understood through a TIS lens. It is proposed that TIS provides a framework to facilitate multi-actor engagement in social innovation responses to the complexity of wicked problems? The goal is to explore if TIS provides a useful framework for understanding the evolution of social innovation projects and enabling more consciously designed and facilitated social innovation with the potential for large-scale, long-term impact. Design/methodology/approach – The research uses a case study methodology in which 10 NBS projects in 3 European cities are examined and compared to the expected features of a TIS as proposed by anonymised for the review process (2018; 2019) Findings – Of the 10 NBS projects, only 3 were “TIS-like”, each of which was targeting wicked problems in the city/community. As only one of the remaining 7 projects was aimed at a wicked problem, the authors concluded that the TIS framework may be best suited to those social innovations that address one or more wicked problems and that NBS projects may not display this feature. Research limitations/implications – The authors conclude with a reflection on theoretical insights arising from applying the TIS framework to NBS in particular, and social innovation generally – and proposes the next steps in developing the TIS framework in relation to social innovation. Originality/value – This paper applies a new complexity framework to empirical data that have not been examined previously. This analysis contributes to the development of a new framework for designing and analysing complex social innovation initiatives and challenges existing theories presenting NBSs as addressing complex “wicked” problems.
PUBLISHED
Keywords: Complexity; Social innovation; Nature-based solutions; Temporary innovation system; Inclusive Society; International Development; Smart & Sustainable Planet; COMPLEXITY; NATURE-BASED SOLUTIONS; Social Innovation; Temporary Innovation System; Justice and safeguarding